Studi Komparatif Getaran Pada Sepeda Motor Saat Kondisi Standar Dan Hasil Konversi Ke Motor Listrik - Yadi Heryadi; Adi Harmanda; Ghany Heryana; Amri Abdulah (Jurnal Teknologika, 2025)
A potential solution to mitigate exhaust emissions and air pollution is converting conventional motorcycles into electric ones. This study carried out the conversion of a gasoline-powered motorcycle to an electric motorcycle and analyzed changes in its dynamic characteristics through measurements of the center of gravity, suspension load distribution, and two-degree-of-freedom vibration response. The methodology involved determining the motorcycle’s center of gravity before and after conversion using the moment-of-force approach and conducting vibration analysis with a two-degree-of-freedom undamped model. Tests were performed in unloaded and loaded conditions with a 70 kg passenger to evaluate the effect of additional mass on suspension performance. Before conversion, the motorcycle’s center of gravity was located at x = 526 mm and y = 147 mm, shifting to x = 577 mm and y = 133 mm after conversion. With a passenger, the center of gravity moved from x = 754 mm and y = 704 mm to x = 762 mm and y = 687 mm after conversion. The total load decreased from 267 kg (74.8 kg front and 192.2 kg rear) to 239.6 kg (66.9 kg front and 172.7 kg rear). The vibration analysis revealed that the main natural frequency slightly increased from ω₁ = 19.507 rad/s (≈3.10 cps) to ω₁ = 19.654 rad/s (≈3.12 cps), while the secondary frequency remained stable at ω₂ = 4.52 rad/s (≈0.71 cps). The amplitude ratio changed marginally from (A/B) = 6.028 m/rad to 6.088 m/rad. Overall, the conversion does not induce significant additional vibration, indicating that the structural dynamics remain stable. However, fine-tuning of battery placement and suspension stiffness is recommended to optimize stability and ride comfort.